SEASONAL VARIATIONS OF THE IONOSPHERE SCINTILLATIONS PARAMETERS OBTAINED FROM THE LONG OBSERVATIONS OF THE POWER COSMIC RADIO SOURCES AT THE DECAMETER WAVE RANGE - Lytvynenko, O. A.; Panishko, S. K. (Одеські астрономічні публікації, 2016)
Observations of the four power cosmic radio sources were carried out on the radio telescope (RT) URAN-4 during 1987-1990 and 1998-2007 at the frequencies 20 and 25 MHz. Effects of ionosphere and in particular existence of intensity fluctuations on the cosmic radio sources records, or scintillations, are essential at the decameter wave range. Long series of the ionosphere scintillations parameters such as indices, periods and spectrum slopes were obtained after observation data proceeding. Behavior of the seasonal variations was investigated on this data. Obtained dependencies were compared with the indices of the solar and geomagnetic activity